EFEKTIVITAS PENGGUNAAN VIDEO PADA MATA PELAJARAN EKONOMI DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SMA SWASTA IMELDA MEDAN - Febriana Jovanka Gultom; Lasma Siagian; Dearlina Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the use of learning media on student learning outcomes at Imelda Private Senior High School, Medan. The background of the study is based on the importance of utilizing appropriate media in the learning process to improve student understanding and engagement. The use of effective learning media is expected to create a more interactive, engaging, and meaningful learning process. The research method used was quantitative with a quasiexperimental approach using a design with data collection techniques through observation, questionnaires, and documentation. The research sample consisted of students selected based on specific criteria in accordance with the research objectives. The data obtained were analyzed using statistical techniques to determine the relationships and influences between variables. The results showed that the use of learning media had a positive impact on student learning outcomes. This was evidenced by the results of the regression coefficient/t-test, with a significance value of 0.000 (<0.05), and the N-Gain interpretation showed an average increase of 83.33%. Systematically designed learning media can improve student learning outcomes. Thus, optimal use of learning media can be an effective strategy in improving the quality of the learning process and outcomes.